Angola : 2018 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Angola. (IMF Staff Country Reports; Country Report ;, 2018)
This 2018 Article IV Consultation highlights that lower oil prices since mid-2014 have placed the Angolan economy under stress. The authorities initially reacted to the oil price shock with significant fiscal tightening and exchange rate adjustments coupled with foreign exchange quantitative restrictions. The policy mix in the run-up to the August 2017 elections-fiscal expansion and pegged exchange rate-led to a further erosion of fiscal and external buffers. President Joao Lourenco has focused attention on improving governance and restoring macroeconomic stability. The government's macroeconomic stabilization program envisages: upfront fiscal consolidation; greater exchange rate flexibility; reducing the public debt-to-GDP ratio to 60 percent over the medium term; improving the public debt profile; and settling domestic payments arrears.